Influence of Some Î²-Blockers on Erythrocyte Hypotonic Hemolysis - Rudenko, S. V.; Said, M. K.; Volovelskaya, Ye. L. (Problems of Cryobiology and Cryomedicine, 2010)
Influence of some Î²-blockers on human erythrocyte hypotonic hemolysis was investigated. Hemolysis extent and rate were shown to be inhibited as blockers concentrations increased in hypotonic medium within the concentration range studied. By contrast red blood cells pretreated with blockers became more sensitive to hypotonicity and less sensitive to blockers under the same conditions. The analysis shows that this effect cannot be explained by increased surface-volume ratio of cells, increased cation permeability of membranes or changes in membrane fluidity. It is assumed that blocking effect is attributed to stimulated repair of fluctuating membrane pores, which are formed at an earlier stage of hypotonic hemolysis.